Arbuscular Mycorrhizal Fungus "Rhizophagus irregularis" impacts on physiological and biochemical responses of ryegrass and chickpea plants under beryllium stress. (15th December 2022) - Sheteiwy, Mohamed S.; El-Sawah, Ahmed M.; Korany, Shereen Magdy; Alsherif, Emad A.; Mowafy, Amr M.; Chen, Ji; Jośko, Izabela; Selim, Samy; AbdElgawad, Hamada
Abstract: Heavy metals such as beryllium (Be) have been identified as toxic for plants with a negative impact on plant growth. Therefore, there is an urgent need for environmentally friendly techniques to reduce Be toxicity on plant growth and productivity. To this end, arbuscular mycorrhizal fungi (AMF) are widely applied to induce plant growth and stress tolerance. However, how AMF-plant symbiosis can support plants under Be stress has not been studied. Accordingly, we investigated the physiological and biochemical responses of AMF inoculated ryegrass and chickpea plants to Be stress. The associated changes in Be uptake and accumulation, photosynthesis, oxidative stress, carbon and nitrogen metabolism were studied. Soil contamination with Be induced higher Be accumulation, particularly in ryegrass, which consequentially reduced plant growth and photosynthesis. However, photorespiration and oxidative damage (H2 O2 accumulation, lipid oxidation, and LOX activity) were increased, mainly in ryegrass. In both plant species, AMF inoculation reduced Be accumulation and mitigated growth inhibition and oxidative damage, but to a more extent in ryegrass. This could be explained by improved photosynthesis as well as the upregulation of osmoprotectants i.e., sucrose and proline biosynthesis pathways. The increase in proline level was consistent with higher nitrogen (N) metabolism as reflected by N level and nitrate reductase. Species-specific responses were recorded and supported by principal component analysis. This study provided insight into the mechanism of AMF's impact on Be-stressed ryegrass and chickpea plants. Hence, the current research suggested that AMF inoculation could be used as a viable strategy to mitigate Be phytotoxicity in ryegrass and chickpea plants. Graphical abstract: Image 1 Highlights: Ryegrass was more tolerant than chickpea to Be stress. Inoculation with AMF reduced Be phytotoxicity and enhanced photosynthesis of both plants. AMF inoculation reduced Be accumulation and mitigated growth inhibition and oxidative damage. Sucrose and proline biosynthesis pathways were upregulated under Be stress. Nitrogen level and nitrate reductase activity were induced by AMF under Be stress.